The Benefits of Friendliness: The Consequences of Positive Interpersonal Relations for Interstate Politics. Issue 2 (16th February 2022) - Heimann, Gadi; Kampf, Zohar
Abstract: While most international relations (IR) scholars tend to minimize the effect of relations between statespersons on foreign policy, this article argues that interpersonal relationships have more weight than the literature suggests. On the basis of twenty-one interviews conducted with senior Israeli statespersons, we propose a two-level model-linking positive interaction between statespersons and actual consequences at the state level. At the personal level, positive interactions can create receptiveness, build trust, facilitate accessibility and availability, and advance personal commitment. Translating these outcomes into consequences at the state level is mediated either by persuasion or by commitment. If persuasion is effective or there exists a high level of personal commitment, statespersons are more likely to succeed in mobilizing international support, removing obstacles to agreements, gathering sensitive information, and diffusing interstate tension. We conclude by discussing the limitations and advantages of good personal relations between statespersons and their implications for IR practice and theory.